The influence of service delivery failures, service recovery and perceived values on customer behavioural intentions in Malay restaurants / Zulhan Othman - Othman, Zulhan (2015)
Undeniable in restaurant operation service delivery failures occurred when service delivery performance does not meet the expectations of customers and classified as either pertaining to the outcome or process. A process failure happened when core service carried in a flawed or incomplete way, resulting in poor benefit and instigating in reduction of economic resources such as money, time, status or esteem to the customer. Knowing failures will occur even in the finest restaurant, it is imperative therefore for the restaurant to make provisions for recovery of these unfavourable instances and the provisions that restaurant makes are known as service recovery. Restaurant ability to recover from service delivery failure is an essential element of the whole service delivery system with significant implications as it is recognized to provide opportunities to decrease costs, improve customer experience and increase customer satisfaction. The effective service recovery not only corrects the service delivery failures, but also builds and maintains strong relationships which ultimately lead to behavioural intentions, including revisiting and word of mouth. In contrary, as to why customers are found of still patronizing some of the restaurants despite providing fewer recovery processes. It is therefore conjectured that the role of positive perceived values may influence customers repeat purchase behaviour or the underlying reasons that cause this causation. This study empirically investigates the causal relationship among service delivery failures, service recovery and perceived values with satisfaction and behavioural intentions of customers towards Malay medium restaurants. A mixed method of qualitative and quantitative investigation through interview with selected restaurant operators and questionnaire survey among the restaurant customers was opted. Through interview with 18 restaurant operators, occurrence of service delivery failures and service recovery as well perceived values in Malay medium restaurants as central issue of this study were identified. The quantitative approach in this study structured through survey questionnaire wit customers who had visited and experienced service delivery failures when dining at pre-identified Malay restaurants in Klang Valley. With 481 respondents, the data analyses were conducted by a process of multivariate analysis using structural equation modelling (SEM) via AMOS (Analysis of Moment Structures). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were initially performed to validate the scales. Five dimensions of the overall measurement model were generated and tested in compliance with stringent purification process for the models. The results of structural modelling provide evidence that three dimensions of service delivery failures, service recovery and behavioural intentions were significantly related and the relationship between service recovery and customer satisfaction were not significantly related. However, the strength of the relationship between service delivery failures and customer satisfaction would be altered by the presence of perceived value. In other word, perceived value mediates the relationship between service delivery failure and customer satisfaction. With this finding, the restaurant operators should not therefore ignore or being ignorant on the perceived value, but highly conversant with it as those elements could be used in retaining the customers despite having a slight service failure and slacking in service recovery.